PRAKTIK PERSEKONGKOLAN TENDER DALAMPENGADAAN PAKET PEMBANGUNAN REVETMENT DANPENGURUGAN LAHAN - Vira Fakhira (2023)
The state and business actors are parties that are negatively affected by a conspiracy in a tender. Even though it has been regulated and prohibited explicitly in Law Number 5/1999, there are still business actors who conspire in tenders. This study aims to explain how the tender conspiracy occurred in the procurement of the revetment development package and landfill at the Popoh Fishing Port and the KPPU's responsibility for the practice of tender conspiracy in the procurement of the revetment development package and landfill. This study uses a normative juridical research method using a statutory approach (Statue Approach), namely Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition and a case approach (Case Approach), namely Decision Number 25/KPPU-I/ 2020 regarding Alleged Practices of Conspiracy in the Tender for Procurement of Revetment Development Packages and Landfilling at the Popoh Fishing Port, Tulungagung Regency. The results of this study indicate that the practice of conspiracy continues to occur due to factors such as the abuse of power by the tender committee, weak supervision by the Government Goods and Services Procurement Policy Agency or LKPP and the absence of strict sanctions imposed on tender committees who commit abuse of power. Then KPPU is responsible for the practice of bid rigging in the construction of revetments and landfills by carrying out investigations, examinations and imposing penalties in the form of administrative sanctions to business actors who are proven to have committed violations in this case the tender conspiracy. Then KPPU is also responsible for making preventive efforts to reduce the occurrence of violations in this case the tender conspiracy case so as to create a healthy business climate in Indonesia. The government is expected to tighten supervision on business competition in Indonesia by referring to Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.